2020
DOI: 10.1111/1440-1681.13242
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of the endothelium and constriction of the isolated rat's middle cerebral artery in low sodium environment in the presence of vasopressin

Abstract: Hyponatraemia, a water–electrolyte disorder diagnosed in patients with subarachnoid haemorrhage (SAH), increases a risk of persistent vasospasm. In majority of cases, hyponatraemia results from inappropriate secretion of vasopressin (AVP). The effect of AVP‐associated hyponatraemia on cerebral vasculature is unknown. The present study aimed to elucidate the role of AVP in the response of the middle cerebral artery (MCA) of the rat to hyponatraemia. Isolated, cannulated, and pressurized rat MCAs were perfused/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
(90 reference statements)
0
10
0
Order By: Relevance
“…Our previous studies have shown that the constriction of the MCA in AVP‐associated hyponatremia depends on endothelin‐1 and thromboxane A 2. 40 The mechanism of the constriction of parenchymal arterioles during AVP‐associated hyponatremia is unknown at present. Taking into consideration substantial functional and structural differences between parenchymal arterioles and pial arteries 14,15,19,20 it is unlikely that the mechanism of constriction of both types of vessels during AVP‐associated hyponatremia is identical.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that the constriction of the MCA in AVP‐associated hyponatremia depends on endothelin‐1 and thromboxane A 2. 40 The mechanism of the constriction of parenchymal arterioles during AVP‐associated hyponatremia is unknown at present. Taking into consideration substantial functional and structural differences between parenchymal arterioles and pial arteries 14,15,19,20 it is unlikely that the mechanism of constriction of both types of vessels during AVP‐associated hyponatremia is identical.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have found that lowering the extracellular concentration of Na + to the level diagnosed in symptomatic patients with hyponatremia (121 mmol L − 1 ), elicits dilation of the rat middle cerebral artery [22]. In the present study, we sought to identify the possible mechanism responsible for this dilation.…”
Section: Introductionmentioning
confidence: 87%
“…Isolation and mounting of the MCA Middle cerebral arteries (n = 76) were isolated and mounted in the organ chamber according to the procedure as described [22]. Brie y, MCA was dissected and cleaned of connective tissue.…”
Section: Methodsmentioning
confidence: 99%
“…In the cerebral circulation, vasopressin can cause either increase of the blood flow through an action mediated by V2Rs [85] or restriction of the flow, presumably through stimulation of V1Rs. Interestingly, it appears that the vasoconstrictory action of vasopressin in the cerebral circulation may predominate in hyponatremia, which is an unavoidable attribute of SIADH [168,169]. The traumatic brain injury which is associated with hypoxia causes significant increase of V1aR in the frontoparietal cortex [104].…”
Section: Function Of Vasopressin System In Cardiovascular Diseasesmentioning
confidence: 99%